A review of the 5-Choice Serial Reaction Time (5-CSRT) task in different vertebrate models. (December 2016) - Fizet, Jonas; Cassel, Jean-Christophe; Kelche, Christian; Meunier, Hélène
Highlights: The 5-CSRT paradigm considered as one of the most valuable measure of attention. Investigation of changes done to optimize the original 5-CSRT task on rodents. Review and analyze of methodological adaptations of the 5-CSRT to non-rodent models. Discussion on touchscreen implementation in 5-CSRT paradigm. Discussion on the interest of the 5-CSRT task for future cognition research. Abstract: Within cognitive and behavioural research, the 5-Choice Serial Reaction Time task is widely recognized as a valuable test of attention in rats. However, technical and methodological developments required for extending its usefulness are still at an early stage. In view of advances in knowledge about cognition and other areas of biology, issues surrounding attention are increasingly important, and appear to require new methodological approaches. These changes may concern (i) the evolution of the protocol itself, (ii) adaptations in how tasks are implemented (e.g. use of new technologies such as touchscreens), and (iii) applying existing tasks to species presenting an emerging potential. From a primarily methodological perspective, this review focuses on work that has successively built upon the original 5-CSRT task. We address the strengths and weaknesses of new approaches as well as some of the new possibilities they offer.